2020
DOI: 10.26719/emhj.20.140
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting hookah tobacco smoking among females in the Islamic Republic of Iran: a qualitative study

Abstract: Background: The prevalence of hookah smoking in the Islamic Republic of Iran is increasing among females, especially in the southern cities. Aims: The aim of this study was to investigate the factors influencing hookah tobacco smoking among females in the Islamic Republic of Iran. Methods: In this qualitative study, 52 females who use hookah were selected (25–71 years old) from the cities of Evaz and Gerash and were interviewed. The participants were selected using purposive sampling and the data were gathered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Such findings were also extended to urban Jordanians. This might be attributed to the influence of marketing power, social media, encouraging environment in cafes, social activity during large gatherings, the freedom of females to access waterpipe tobacco as easily as males, and the belief that waterpipe smoking is less harmful than cigarette smoking [36,37]. Furthermore, the use of waterpipe tobacco for women is considered more socially acceptable compared to cigarette smoking, which ultimately increases the prevalence of waterpipe smoking among females in Arab countries [32].…”
Section: Discussionmentioning
confidence: 99%
“…Such findings were also extended to urban Jordanians. This might be attributed to the influence of marketing power, social media, encouraging environment in cafes, social activity during large gatherings, the freedom of females to access waterpipe tobacco as easily as males, and the belief that waterpipe smoking is less harmful than cigarette smoking [36,37]. Furthermore, the use of waterpipe tobacco for women is considered more socially acceptable compared to cigarette smoking, which ultimately increases the prevalence of waterpipe smoking among females in Arab countries [32].…”
Section: Discussionmentioning
confidence: 99%
“…The results of these studies may be partly explained by the fact that cigarette smoking is not very socially acceptable for females in Middle Eastern countries, while narghile smoking is considered acceptable in social culture [7] and is usually practiced with family and friends [22]. Typically, it is the duty of females in the household to PLOS GLOBAL PUBLIC HEALTH PLOS GLOBAL PUBLIC HEALTH prepare the narghile, and in its preparation they must inhale it to make sure it is well prepared [23]. In two different studies, females have reported that the exposure of having to prepare the narghile led them to acquiring the habit of smoking narghile [24,25].…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…Typically, it is the duty of females in the household to PLOS GLOBAL PUBLIC HEALTH PLOS GLOBAL PUBLIC HEALTH prepare the narghile, and in its preparation they must inhale it to make sure it is well prepared [23]. In two different studies, females have reported that the exposure of having to prepare the narghile led them to acquiring the habit of smoking narghile [24,25]. This could partly explain the social acceptance of narghile for females as compared to cigarette smoking.…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…Unfortunately, in Iran, various tools with a highly diverse and attractive appearance, along with hookah shops have attracted young people. Industrial and herbal drugs are freely sold in newsstands and some luxury supermarkets (10,11). In recent years, with the spread of young people turning to industrial narcotics, some people, thinking of facilitating the process of using these narcotics, have designed devices for smoking.…”
mentioning
confidence: 99%